Moult strategies of oystercatchers (Haematopidae) in New Zealand, Australia and South Africa - Bate, Taylyn (Department of Biological Sciences, 2024)
While there are a number of studies that have examined the moult strategies of migrant waders (Charadrii), only a few have focused on non-migrant waders. As part of a collection of papers that have analysed moult using the Underhill-Zucchini moult model, we used this method to observe the moult strategies of species within the family Haematopidae. Our data includes a combination of previously acquired ringing data and that which we collected, along with contributions by citizen scientists, in the form of photographic records. The first chapter provides an introduction to the study, placing it within the context of comparable research, and placing moult within the context of the birds' important life stages. Our second chapter focuses on the Australian Pied Oystercatcher Haematopus longirostris, of which we completed a detailed analysis of the wing and feather moult. Within chapters 3-6 we examine the wing moult strategies of the Sooty Oystercatcher H. fuliginosus of Australia, the South Island Pied Oystercatcher H. finschi and Variable Oystercatcher H. unicolor of New Zealand, and the African Oystercatcher H. moquini of South Africa. With no long-distance movements, these oystercatchers are free to devote more time and energy towards other stages in their life cycle: breeding and moult. We identified the moult parameters of start date, standard deviation in start date, duration and end date for each of the five species. We acquired the relative feather masses and used these in the conversion of the moult scores to proportion feather mass grown (PFMG). The final chapter synthesizes the work, consisting of a comparison and identification of the similarities and differences between the species' moult strategies, and possible reasons for these. We approach the conclusion that further research is needed on the strategies of moult for resident waders, and this may be achieved successfully through the use of digital photography. With an expanding knowledge of the parameters of moult, there is opportunity for even more discoveries into these birds' lives, which will have benefits for their conservation.